2021
DOI: 10.3390/ijerph18094613
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Screen Time Behaviors during the COVID-19 Pandemic in the U.S.: A Mixed-Methods Study among a Diverse Population-Based Sample of Emerging Adults

Abstract: Understanding how screen time behaviors changed during the COVID-19 pandemic is important to inform the design of health promotion interventions. The purpose of this study was to quantify and describe changes in recreational screen time from 2018 to 2020 among a diverse sample of emerging adults. Participants (n = 716) reported their average weekly recreational screen time in 2018 and again during the pandemic in 2020. Additionally, participants qualitatively reported how events related to COVID-19 had influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
5
45
0
2
Order By: Relevance
“…Screen time has been shown to be negatively associated with social development [5], social quality of life [6] and social connectedness in youth [7] and adults [10]. However, COVID-19 lockdown restrictions resulted in screens being one of the only methods for people to communicate with others outside their house, and the desire to connect with others has been noted as a driver for this change in screen time [29]. Importantly, the magnitude of differences in screen use for social communication between pre-lockdown and during lockdown restrictions was larger amongst children compared to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Screen time has been shown to be negatively associated with social development [5], social quality of life [6] and social connectedness in youth [7] and adults [10]. However, COVID-19 lockdown restrictions resulted in screens being one of the only methods for people to communicate with others outside their house, and the desire to connect with others has been noted as a driver for this change in screen time [29]. Importantly, the magnitude of differences in screen use for social communication between pre-lockdown and during lockdown restrictions was larger amongst children compared to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable attention has focused on screen time as a source of elevated distress during the pandemic (Browning et al, 2021;Richtel, 2021;, punctuated by numerous anecdotal reports of people experiencing shock at the increase in their own smartphone and social media use. In a community sample of emerging adults, self-reported recreational screen time increased by 2.6 hours per week, on average, during the pandemic compared to two years earlier (Wagner et al, 2021). In an effort to cope with COVID-19 stress, 79.2% of undergraduate students reported turning to social media-which was correlated with reports of more negative effects of COVID-19 on stress-and 60.4% reported connecting with friends and family using video chat-which was uncorrelated with negative effects of COVID-19 on stress (Prowse et al, 2021).…”
Section: Undergraduate Stress and The Covid-19 Contextmentioning
confidence: 89%
“…It should be indicated that increased screen time, which is commonly observed during the COVID-19 pandemic [68], may also be an important factor influencing food habits. A study conducted in a Spanish population of children and adolescents during the COVID-19 pandemic revealed that increased screen time was associated with worse dietary behaviors, including lower intake of fruit, vegetables, fish, pulses, and nuts, but higher intake of fast foods and sweets [69].…”
Section: Discussionmentioning
confidence: 99%